Políticas de fomento a la competitividad de la pequeña empresa - Vargas, Braulio (2007)
In 2003 the Peruvian government launched a second wave of decentralization and devolution initiatives to the sub-national governments. The move aimed at fostering development, economic growth and job creation with a strong focus on small companies. However, evidence shows these efforts failed because properly planned policies linked to development objectives were lacking. A reference framework is proposed to design local policies that will add economic momentum, relate the local business network to external systems, and create wellbeing by fostering small business competitiveness. To help identify several types of development measures, the paper proposes to take account of the relation between the business activity and its territory, the key factors of success of innovative companies, and the business’s life cycle as related to the potential for innovation and growth